METODE GURU DALAM MENINGKATKAN KONSENTRASI ANAK YANG MENGALAMI GANGGUAN PEMUSATAN PERHATIAN DAN HIPERAKTIFITAS (GPPH/ADHD) DALAM KEGIATAN BELAJAR - Fithri Ainun Nisa; Nurul Khotimah (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This research focuses on the methods used by the teacher in improving the concentration process in children who experience impaired concentration. The reason we chose the theme in this study is that concentration is important in the learning process to capture the information given to the teacher, so that it can achieve the learning objectives, but there are children who have difficulty concentrating, therefore we want to know and understand how the method which is used by the teacher in training the concentration of children with impaired concentration / concentration. Writing this research journal aims to share understanding of the methods that need to be done by teachers and parents in honing the concentration of children, especially children who experience impaired concentration. The authorship method used was interviews and documentation of the subject's learning outcomes. The conclusion of this research is the interviewees used sound playing methods such as touch / sensory games, radio games, and verse contours.Â Keywords: early child; concentration; method; ADHD.This research focuses on the methods used by the teacher in improving the concentration process in children who experience impaired concentration. The reason we chose the theme in this study is that concentration is important in the learning process to capture the information given to the teacher, so that it can achieve the learning objectives, but there are children who have difficulty concentrating, therefore we want to know and understand how the method which is used by the teacher in training the concentration of children with impaired concentration / concentration. Writing this research journal aims to share understanding of the methods that need to be done by teachers and parents in honing the concentration of children, especially children who experience impaired concentration. The authorship method used was interviews and documentation of the subject's learning outcomes. The conclusion of this research is the interviewees used sound playing methods such as touch / sensory games, radio games, and verse contours.Â Keywords: AUD, concentration, method, ADHD.